2001
DOI: 10.1152/ajpgi.2001.281.5.g1322
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin vanilloid receptor-1 mediates substance P release in experimental pancreatitis

Abstract: We examined whether the capsaicin vanilloid receptor-1 (VR1) mediates substance P (SP) release from primary sensory neurons in experimental pancreatitis. Pancreatitis was achieved by 12 hourly injections of caerulein (50 microg/kg ip) in mice. One group received capsazepine (100 micromol/kg sc), a competitive VR1 antagonist, at 4-h intervals. Neurokinin-1 receptor (NK1R) internalization in acinar cells, used as an index of endogenous SP release, was assessed by immunocytochemical quantification of NK1R endocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 32 publications
(45 reference statements)
5
65
0
Order By: Relevance
“…TRPV1 mRNA and protein are upregulated in animals with pancreatitis, in line with enhanced responses by pancreatic afferent neurons to capsaicin (Xu et al, 2007;Schwartz et al, 2011Schwartz et al, , 2013Zhu et al, 2011). Consistent with these studies, capsaicin-treated animals are less susceptible to pancreatitis and treatment with the TRPV1 antagonist capsazepine or resiniferatoxin-induced denervation protects against caerulein-induced pancreatitis (Nathan et al, 2001;Noble et al, 2006). TRPA1-positive afferent nerve fibers innervate the pancreas and respond to the TRPA1 activators allyl isothiocyanate and endogenous agonists produced in pancreatic inflammation (15dPGJ2 and 4-HNE), and responses are attenuated by TRPA1 inhibitors or in trpa1 2/2 mice (Ceppa et al, 2010;Schwartz et al, 2011Schwartz et al, , 2013.…”
Section: B Transient Receptor Potential Channels Pancreatitis and supporting
confidence: 66%
“…TRPV1 mRNA and protein are upregulated in animals with pancreatitis, in line with enhanced responses by pancreatic afferent neurons to capsaicin (Xu et al, 2007;Schwartz et al, 2011Schwartz et al, , 2013Zhu et al, 2011). Consistent with these studies, capsaicin-treated animals are less susceptible to pancreatitis and treatment with the TRPV1 antagonist capsazepine or resiniferatoxin-induced denervation protects against caerulein-induced pancreatitis (Nathan et al, 2001;Noble et al, 2006). TRPA1-positive afferent nerve fibers innervate the pancreas and respond to the TRPA1 activators allyl isothiocyanate and endogenous agonists produced in pancreatic inflammation (15dPGJ2 and 4-HNE), and responses are attenuated by TRPA1 inhibitors or in trpa1 2/2 mice (Ceppa et al, 2010;Schwartz et al, 2011Schwartz et al, , 2013.…”
Section: B Transient Receptor Potential Channels Pancreatitis and supporting
confidence: 66%
“…Sensory neuron ablation attenuates inflammation in models of pancreatitis, suggesting these neurons provide proinflammatory signals (8,10,11,13,14,27). To examine how sensory neurons impact PDAC initiation and progression, we first determined if neonatal capsaicin had direct effects on pancreatic cells because previous studies using cancer-derived cell lines showed it affected apoptosis and proliferation (28)(29)(30)(31)(32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the documented role of sensory neurons in the pathogenesis of pancreatitis (8)(9)(10)(11)(13)(14)(15), a known contributor to the pathogenesis of PDAC, we hypothesized that sensory neurons innervating the pancreas provide key proinflammatory inputs that support the early stages of tumorigenesis. Here, using GEMs of PDAC, we provide evidence that bidirectional communication between the pancreas and sensory neurons is active well before the establishment of tumors.…”
mentioning
confidence: 99%
“…NK-1 and NK-3 receptors exhibit marked differences in the rate of resensitization and in their ability to colocalize with isoforms of ␤-arrestins (determined by domains in intracellular loop 3 and the COOH tail), and these differences could have important functional implications. CKinduced SP release activates subsequent NK-1 receptor endocytosis in acinar cells (22). After activation, NK-1 receptors interact with ␤-arrestins 1 and 2 with high affinity, internalize rapidly, but are slowly resensitized (28).…”
Section: Discussionmentioning
confidence: 99%